2017
DOI: 10.1039/c7ra08879e
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-ulcerogenic effect of KFP-H008 against ethanol-induced gastric ulcerviap38 MAPK/NF-κB pathway

Abstract: KFP-H008, a novel potassium-competitive acid blocker developed for the treatment of acid-related diseases, has been reported to inhibit gastric acid secretion effectively, while its effects on gastric ulcer have not been previously explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…There increasing IL-6 and TNF-α levels in gastric tissue can be attributable to the necrotizing effects of ethanol in the model group. These results of our study showed that pretreatment and treatment with NRNC-CDs could remarkably alleviate in ammation symptoms by suppressing the production of TNF-α and IL-6, which was consistent with previous ndings [36,37].…”
Section: Discussionsupporting
confidence: 93%
“…There increasing IL-6 and TNF-α levels in gastric tissue can be attributable to the necrotizing effects of ethanol in the model group. These results of our study showed that pretreatment and treatment with NRNC-CDs could remarkably alleviate in ammation symptoms by suppressing the production of TNF-α and IL-6, which was consistent with previous ndings [36,37].…”
Section: Discussionsupporting
confidence: 93%
“…35 The activation of major subgroups in the MAPK family regulates the expression of pro-inflammatory mediators, a phenomenon that has been reported in EtOHinduced gastric ulcer in mice. 6,14,34,36 In this study, we confirmed that the MAPKs were activated in gastric tissues of EtOH-treated mice. However, the pretreatment of EF-2001 dose dependently suppressed the phosphorylation of MAPKs in the gastric tissues.…”
Section: Discussionsupporting
confidence: 77%
“…Excessive NO generated by iNOS deleterious effects on the pathophysiological conditions of gastric ulcer. 3,34 In the present study, the EtOHtreated group showed an increased phosphorylation of p65NF-kB with upregulation of pro-inflammatory mediators, COX-2, TNF-a, and iNOS with increased NO levels in the gastric tissues. However, EF-2001treated mice notably exhibited suppressed phosphorylation of p65NF-kB, with the accompanying downregulated expression of pro-inflammatory mediators and gastric NO levels in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations